PENGEMBANGAN INFRASTUKTUR TERMINAL PENUMPANG PADA PELABUHAN BANDAR BINTAN TELANI (BBT) DALAM MENDUKUNG PARIWISATA PULAU BINTAN - Triani Octavia; Bambang Triatmodjo; Sigit Priyanto (TEKNISIA, 2020)
An evaluation of the condition and performance of the BBT Port needs to be carried out because of the significant increase in the number of tourist visits to the Bintan Beach International Resort area. Still, since its inauguration in 1994, the port has not changed much. Passenger terminal needs are commonly defined through projections using the exponential trend method based on ship and visitor flows in the last five years. A port performance is based on BOR (Berth Occupancy Ratio) calculation. In contrast, for the performance evaluation of passenger terminal services is based on the perception of tourists as passenger terminal users obtained from the questionnaire results with a Likert scale and the Importance Performance Analysis (IPA) method from the IPA, interviews with the BBT port manager, are conducted by using the Strength Weakness Opportunities Threats (SWOT) method to formulate the development strategy. The analysis result shows that it needs to increase the waiting area up to 613 m² in 2033, and the parking area of 17,173 m², while the BOR at the BBT port is still in a proper category, by  24.11% of the UNCTAD 50% requirement. In evaluating the passenger satisfaction to the port services, the improvement focuses on the priority quadrant, namely the physical condition of the BBT port facilities. Next, formulating a development strategy in terms of physical aspects and management to adjust the passenger needs, and the BBT port is ready to face business competition in the future.